Konsep Pembenaran Dalam Roma 5:1-11 - Eni Lestari (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2022)
The Book of Romans talks a lot about justification. Paul tells us that all humans have sinned. Meanwhile, wrath is a very terrible danger to sinners, that's why justification is a very meaningful gift for them. And the good news is that the loving God doesn’t allow humans to crumble in His wrath. God made a project for the salvation of man and Christ became the means of redemption that would enable man to be free from God's wrath. For those who are willing to accept His sacrifice, Jesus takes their place, where they are supposed to be punished. So that the justified have peace with God, access to God, glory in suffering and assurance of freedom from His wrath. The death of Jesus, in the past has liberated believers, is now giving hope, and in the future is ensuring the believers' salvation.